(untitled) (Global Journal of Management and Business Research, 2017)
The term agriculture is an essential organ of the economy of Bangladesh. In order to ensure long-term food security, a cost-effective, sustainable and environment-friendly agricultural system is very decisive. Agricultural sector plays an irrefutable role in achieving the overall growth and development of the economy of Bangladesh. Agricultural credit plays an inevitable role in agricultural productivity, since it has increased the quantity and quality of inputs used in production process. Timely and adequate flow of agricultural credit is tremendously important for Agricultural productivity. This paper investigates the performance of overall agricultural credit of banks over time; evaluate the performance of agricultural credit of various types of banks in Bangladesh, analyze performance of agricultural credit disbursed to agricultural sub-sector and reveals status of the beneficiaries of agricultural credit. This study collected time series data from various source and analyze in a meaningful way to discover the true performance of agricultural credit of banks in Bangladesh.